Bioactive compounds, antioxidant activity and growth behavior in lettuce cultivars grown under field and greenhouse conditions - Lanza Volpe, Melisa (2021)
Lettuce (Lactuca sativa L.) is one of the most important leafy greens worldwide. The nutri-tional value of its edible leaf depends on different factors including type and growing conditions.The aim was to determine the bioactive compounds content, antioxidant activity and growth be-havior of twenty-two lettuce genotypes, cultivated under field and greenhouse conditions. Totalphenolic compound, chlorophylls, carotenoids, anthocyanin contents and antioxidant activitieswere analyzed by spectrophotometric methods. Data were analyzed by analysis of variance(ANOVA). Significant differences between bioactive compounds, antioxidant activity and growthbehavior were found among cultivars and morphological types, for both growth conditions. Carot-enoid and chlorophyll content was higher in greenhouse conditions for all genotypes. In field pro-duction, butterhead and iceberg lettuces showed lower content of these bioactive compounds. Thered-pigmented Falbala cultivar from field production showed the highest level of polyphenols andanthocyanin. Meanwhile, in greenhouse conditions, the oak leaf cultivar Grenadine displayed thehighest concentration of these phenolic compounds. The iceberg type lettuce showed the lowestpercentages of antioxidant activity in both environments. The results showed the effect of growingconditions and the high variability in lettuce bioactive compounds content and antioxidant activityamong the different types.